Regorafenib for patients with metastatic colorectal cancer who progressed after standard therapy: results of the large, single‐arm, open‐label phase IIIb CONSIGN study - Van Cutsem, Eric; Martinelli, Erika; Cascinu, Stefano; Sobrero, Alberto; Banzi, Maria; Seitz, Jean‐François; Barone, Carlo; Ychou, Marc; Peeters, Marc; Brenner, Baruch; Hofheinz, Ralf-Dieter; Maiello, Evaristo; et al. (The oncologist, 2019)
This article reports the results of the CONSIGN study, which was designed to characterize the safety of regorafenib in a large patient population, estimate progression‐free survival, and provide patients with treatment‐refractory metastatic colorectal cancer access to regorafenib before market authorization.